Global Icons of Peace: The Enduring Legacy of Gandhi and Mandela in Contemporary Politics - Dr. Awadhesh Kumar Singh, Abhishek Kumar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Mahatma Gandhi and Nelson Mandela stand out as two of the most impactful figures in contemporary history, renowned for their unwavering dedication to peace, justice, and human rights. Their legacies transcend their individual countries, impacting global movements focused on democracy, racial equity, and nonviolent resistance. This paper delves into their lasting influence by comparing their leadership philosophies, political approaches, and effects on current political discussions. Based on theories surrounding nonviolence, transformational leadership, and post-colonial resistance, this study investigates how Gandhi's concept of Satyagraha and Mandela's efforts toward reconciliation have influenced modern governance and methods of conflict resolution. Utilizing empirical data drawn from civil rights movements, peacebuilding endeavors, and surveys on public perceptions, this research underscores the ongoing significance of their ideologies. For example, surveys conducted by the Pew Research Center reveal that 67% of global respondents view nonviolent resistance as an effective means of achieving political and social change, echoing Gandhi's principles. Additionally, data from the United Nations indicate that countries employing reconciliation processes inspired by Mandela's approach see a 25% decrease in post-conflict violence.